(untitled) (Revista Internacional de Folkcomunicação, 2021)
The article proposes an interconnection between the studies of Culture and Politics, taking as a case for analysis the passage of Lampião´s band through the city of Mossoró and how the band was expelled by its greatest local authority, Mayor Rodolfo Fernandes. This local historical fact is revived, every year, on June 13th, through a play, presented in a public square, which helps to reinforce and reinvent, year after year, a revelry and its uses by local politicians and political families, which for years have held power in the city, such as the Rosado family. To this end, we researched, in addition to the play, strings that tell "Lampião saga in Mossoró", Local newspapers about the uses of politicians on the saga of Lampião. We observed that such play helps in perpetuation not only of the imaginary of the city as "land of the brave", but is used by politicians to build their public personas. Lampião; Cangaço; Political Power.